Infectivity of Paragonimus westermani developing in a final host to another final host. - 공윤; Yang, H.J.; Cho, S.Y. (1994)
In the definitive hosts, metacercariae of Paragonimus westermani excyst in host duodenum, penetrate intestinal wall, migrate peritoneal and thoracic cavities, and develop to sexual maturity in 8 weeks. This study was undertaken to examine the age of the maturing P. westermani when their infectivity to the other definitive hosts was retained. On 3, 7, 10, 14, 21 and 28 days after feeding the metacercariae to cats through a gastric tube, the developing worms were harvested. The juveniles of different age were fed again to other experimental cats. One to 12 weeks after the oral-transfer infections, the experimental cats were examined for establishment of infections. In the cats to which 3-day and 7-day old juveniles (grown up to 1.4 mm long) were fed, 31.4% and 22.6% of the transferred worms were found infected. The worms of 10-28 days old were not infective. Early maturing stages grown up to 7 days maintained their infectivity to the other definitive hosts.